Preoperative predictors of Ossicular Discontinuity in non-Cholesteatoma Chronic Otitis Media - Saha, Kanu Lal; Ghosh, Nibash Chandra; Akhtar, Nasima; Talukder, Debesh Chandra (Journal of Dhaka Medical College, 2021)
Background: Though ossicular discontinuity is more common in cases of cholesteatoma, it may happen in non-cholesteatoma COM. The long process of incus is more frequently involved ossicle. Peroperative assessment of ossicular integrity is the gold standard way. But the discontinuity of the ossicular chain can be assumed before surgery by analyzing perforation edge adherent to medial wall and wide air-bone gap The purpose of the study was to find out the preoperative findings which can predict the ossicular discontinuity in non-cholesteatoma cases. Methods: This cross-sectional study was conducted in the department of Otolaryngology-Head & Neck Surgery, Bangabandhu Sheikh Mujib Medical University from January 2013 to June 2014. 81 patients of COM without cholesteatoma were selected as per inclusion and exclusion criteria. Relevant data were collected in a predesigned data collection sheet and analyzed with standard statistical method. Statistically significant inferred for P value <0.05. No groups whose ability to give voluntary informed consent questionable was not included. No potential risks exist in designed this study. Results: Air-bone gap > 40 dB was found in 60% cases of ossicular discontinuity, followed by air bone gap 31-40 dB(20%), 21-30 dB(13.33%) and 11-20 dB( 6.67%) respectively. So ossicular discontinuity was more in higher air-bone gap group and it was statistically highly significant (p<0.001). Perforation edge attached to medial wall where ossicular discontinuity was 93.3% and perforation edge free from medial wall was 6.7%.Ossicular discontinuity was higher when perforation edge was found attached to medial wall which was highly statistically significant (p<0.001). Out of 25 granulation tissue cases ossicular discontinuity was found 21(84%) and ossicular chain intact was found 4(16%). That was statistically significant (p<0.01). Conclusion: Non-cholesteatoma COM may cause ossicular disconnection. Majority ossicular discontinuity found when average air bone gap > 40 dB. Ossicular discontinuity was also found more in cases where there is attachment of perforation edge to medial wall, and presence of granulation tissue. If preoperative information can be gathered to determine whether or not the ossicular chain is intact, the patient can be better informed, counseled for ossiculoplasty before surgery. J Dhaka Medical College, Vol. 29, No.1, April, 2020, Page 47-52